Examining the effects of public participation on residents’ trust in local government: The mediating effect of perceived responsiveness - Ahmed-Nor Mohamed Abdi; Ahmed Ibrahim Nageye; Hassan Omar Sabriye (PLoS ONE, 2025)
Public participation has been widely acknowledged as a mechanism to enhance residents’ trust in governmental institutions. However, the specific pathways through which public participation influences trust via the perceived responsiveness of local government remain underexplored, particularly in post-war settings such as Mogadishu, Somalia. Hence, this study aimed to explore the impact of public participation on residents’ trust in local authorities in Mogadishu, Somalia, through the perceived responsiveness as a mediator in this relationship within the unique context of a post-war country. Data were collected between January 20 and April 30, 2024. This research employed a quantitative online survey to gather data from 446 inhabitants of Mogadishu City, Somalia. The subjects in the study were recruited using a convenient sampling technique. The proposed model was analyzed using covariance-based structural equation modeling (CB-SEM) in SmartPLS version 4 to examine the hypothesized relationships and mediating effects. The findings indicated that perceived public participation positively and significantly predicted both perceptions of responsiveness and residents’ trust in local authorities. The findings also revealed that perceptions of local government responsiveness were directly, positively, and significantly associated with residents’ trust in the city administration. The results ultimately indicated a positive partial mediation effect of perceived local government responsiveness on the association between public participation and residents’ trust in city administration. This study addresses a lacuna in the literature by exploring how perceived public participation influences residents’ trust in city authorities in a post-conflict setting, particularly in Somalia. This underscores the significance of perceived responsiveness as a mediator in enhancing residents’ trust, providing invaluable insights for policymakers and local government officials.